Biomechanical comparison of three-point shoot after and before official basketball rules 2010 (6.25 and 6.75 meters) in basketball - Abdel Hamid Hassan, M.; Tariq Gamal Mohamed Alaa El Deen, T. (World Journal of Sport Sciences, 2011)
This study was all about defining the differences of the angle and line of the parts of the body in the skill of the three-point shot between shooting from 6.25 meters and 6.75 meters, the researchers utilized the descriptive approach and depended on the mechanical analysis by the fast video analysis method. Research sample consisted of 3 international players from the Egyptian First National Team, who are registered in El Gezirah Sporting Club and selected by intentional method as every player had performed 2 three-point shots from 6.25 meters distance and 2 three-point shots from 6.75 meters distance for the new system. As such, the number of attempts subject to analysis is 6 attempts for each of the old and the new systems to make the total number of attempts subject to statistical analysis 12 attempts. Results revealed that standby position of the shooting skill did not change along the change of the shooting distances and for the steadiness of the position of the body at the beginning of shooting, Shooting distance has a direct effect on the velocity of launching; as well the velocity of launching and the distance of launching have an interacting relationship with the angle of ball throwing. The players need preliminary velocity that helps them in the stage of shooting. The players need greater velocity at 6.75 meters distance at the moment of shooting in order to make up for the difference of distance between the 6.25 meters distance and the 6.75 meters distance. With an additional movement of the hand wrist, it gives the player the necessary velocity to starting and the necessary directio